2018
DOI: 10.1016/j.neuint.2017.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Methylated flavonoids as anti-seizure agents: Naringenin 4′,7-dimethyl ether attenuates epileptic seizures in zebrafish and mouse models

Abstract: Epilepsy is a neurological disease that affects more than 70 million people worldwide and is characterized by the presence of spontaneous unprovoked recurrent seizures. Existing anti-seizure drugs (ASDs) have side effects and fail to control seizures in 30% of patients due to drug resistance. Hence, safer and more efficacious drugs are sorely needed. Flavonoids are polyphenolic structures naturally present in most plants and consumed daily with no adverse effects reported. These structures have shown activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
54
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 69 publications
4
54
0
1
Order By: Relevance
“…Pharmacological effects of flavonoids can be accredited to their antioxidant, anti-inflammatory properties or their potential to influence the signalling molecules in various cellular cascades. Flavonoids can interact directly with cellular receptors and proteins (kinases and enzymes), resulting in physiological responses and gene expression alterations that can lead to neuroprotection [17]. In epilepsy, following seizures the antioxidant defence mechanisms are diminished with the generation of free radicals in the brain.…”
Section: Flavonoids and Epilepsymentioning
confidence: 99%
“…Pharmacological effects of flavonoids can be accredited to their antioxidant, anti-inflammatory properties or their potential to influence the signalling molecules in various cellular cascades. Flavonoids can interact directly with cellular receptors and proteins (kinases and enzymes), resulting in physiological responses and gene expression alterations that can lead to neuroprotection [17]. In epilepsy, following seizures the antioxidant defence mechanisms are diminished with the generation of free radicals in the brain.…”
Section: Flavonoids and Epilepsymentioning
confidence: 99%
“…Brain-wide imaging during seizures, in contrast to invasive electrophysiological recordings, increases the likelihood that network patterns will be discovered. To this end, we combined well-established acute seizure (pentylenetetrazole; PTZ; Baraban et al, 2005; Baxendale et al, 2012; Afrikanova et al, 2013; Buenafe et al, 2013; Orellana-Paucar et al, 2013; Rahn et al, 2014; Siebel et al, 2015; Barbalho et al, 2016; Copmans et al, 2018) and non-seizure hyperexcitability (4-aminopyridine; 4-AP) models (Ellis et al, 2012; Kumar et al, 2016; Cassar et al, 2017; Winter et al, 2017) with spinning disk confocal microscopy, enabling fast (20–30 fps) in vivo imaging of network events. Imaging studies were performed at brain-wide and single-cell resolution levels.…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports showed that derivatives of naringenin with methyl groups attached to the C-7 and C-4′ positions exhibited a strong anti-seizures effect in a larval zebrafish model. Thus, sakuranetin and 7,4′-di- O -methylnaringenin were proposed as agents capable of attenuating epileptic attacks [15]. Another derivative, 7- O -butylnaringenin was described as a potent antibacterial agent in the treatment of infections caused by various common pathogens, such as methicillin-resistant Staphylococcus aureus (MRSA) [16] and Helicobacter pylori [17].…”
Section: Introductionmentioning
confidence: 99%